The Economics Material on the Quipper Indonesia YouTube Channel and Its Function as a Learning Media - Sulik Sofinda; Sugeng Santoso (Mauve Journal De Leardu, 2025)
This research explores the Economics material available on the Quipper Indonesia YouTube channel and examines its function as a learning media for senior high schools within the Merdeka Curriculum. Using a descriptive qualitative method, the research analyzed video content in the Economics playlist by comparing it with curriculum standards and learning objectives. Data were collected through observation, video review, and document analysis of government-issued textbooks and syllabi. The findings show that Quipper Indonesia provides Economics material that aligns with topics in high school, such as introduction to economics, markets, economic growth, monetary policy, accounting, and international trade. Although not all curriculum content is fully represented, the videos offer clear explanations, engaging visuals, and contextual examples that support students’ understanding. This demonstrates the channel’s potential as an effective complementary resource in Economics learning. The research concludes that Quipper Indonesia can be integrated into classroom practice, providing teachers with relevant digital media to enrich learning.